Especificación de Componentes MDA para Patrones de Diseño - Martínez, Liliana Inés (2008)
The Model Driven Architecture (MDA) promotes the use of models and model transformations for developing software systems. The idea behind MDA is to manage the evolution from Platform Independent Models to Platform Specific Models that can be used to generate executable components and applications. The concepts of metamodels and metamodel-based model transformations are critical in MDA. In this paper, we analyze how to specify reusable components for design patterns in a way that fit MDA very closely. To define families of reusable components we describe a “megamodel” that refers to metamodels and model transformations organized into an architectural framework. We propose an integration of formal and semiformal specifications to specify MDA mega-components. Our formalization focuses on interoperability of formal languages in Model Driven Development (MDD).